CONTENT AND MEANS OF TEENAGERS’ AESTHETIC EDUCATION DURING EXTRA-CURRICULAR ACTIVITIES - Iryna Palasevych (Людинознавчі студії: Серія Педагогіка, 2019)
PALASEVYCH Iryna – PhD of Pedagogical Sciences, Associate Professor, General Pedagogy and Preschool Education Department, Drohobych Ivan Franko State Pedagogical University, Ivan Franko Str., 24, Drohobych, 82100, Ukraine